Hubungan Tingkat Pendidikan Orang Tua (Ibu) dengan Kepatuhan Pemberian Imunisasi Dasar pada Bayi Usia 0-9 Bulan di Desa Olung Hanangan - Asniwiyah Asniwiyah; Henry Wiyono; Takesi Arisandy (Pusat Riset dan Inovasi Nasional, 2023)
Immunization serves as the most effective and cost-efficient primary preventive measure against infectious diseases. It not only shields individuals from severe ailments but also averts the spread of communicable illnesses. Drawing from data collection, Olung Hanangan Village ranks among the communities with the lowest coverage of fundamental immunization. The insufficiency in basic immunization may arise due to factors like inadequate education and parental adherence to immunization schedules. The level of education shapes the pattern of shifts in parents' health-related behavior, ultimately emerging as a determinant of adherence to scheduled immunizations. Objective: This study aims to examine the correlation between parental (mothers') education levels and adherence to basic immunization for infants aged 0-9 months in Olung Hanangan Village. Method: Employing a quantitative research approach with a correlational research type and a cross-sectional design, this study involves a total of 32 respondents. Data collection employs a questionnaire as the measuring tool, followed by data analysis utilizing the Chi-Square statistical test. Results: The obtained significant value (p-value) is less than the α value, with a significance level set at α = 0.05. The Chi-Square statistical test yields a significant value of Asmp. Sig. (2-tailed) at 0.000. This finding confirms a relationship between parental (mothers') education levels and adherence to basic immunization for infants aged 0-9 months in Olung Hanangan Village. Conclusion: The study's findings underscore a significant link between parental (mothers') education levels and adherence to basic immunization for infants aged 0-9 months in Olung Hanangan Village. Consequently, the active involvement of healthcare personnel remains imperative in the ongoing provision of immunization information to the community.